2013
DOI: 10.3109/13880209.2013.772211
|View full text |Cite
|
Sign up to set email alerts
|

The extract ofCinnamomum cassiatwigs inhibits adipocyte differentiation via activation of the insulin signaling pathway in 3T3-L1 preadipocytes

Abstract: Context: Obesity is associated with a number of diseases with metabolic abnormalities such as type 2 diabetes (T2D). Medicinal plants have been widely used for the treatment of obesity and related complications. Objective: In this study, we investigated the antidiabetic properties of the extract of twigs of Cinnamomum cassia Blume (Lauraceae) (Cinnamomi Ramulus; CR) in 3T3-L1 murine preadipocytes. Materials and methods: 3T3-L1 cells were differentiated into adipocytes for 3 d in insulinconditioned medium and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…Cinnamon decreased lipid accumulation in vitro in 3T3-L1 preadipocytes and the expression of adipogenic transcription factors PPARγ, C/EBPα and SREBP-1c during adipocyte differentiation [102]. In a dose-dependent manner, cinnamaldehyde also decreased visceral fat deposition, partly mediated by the activation of interscapular BAT, as evidenced by the upregulation of UCP1 expression levels, in high fat and high sucrose diet-fed mice [97].…”
Section: Phytochemicals In Obesitymentioning
confidence: 99%
“…Cinnamon decreased lipid accumulation in vitro in 3T3-L1 preadipocytes and the expression of adipogenic transcription factors PPARγ, C/EBPα and SREBP-1c during adipocyte differentiation [102]. In a dose-dependent manner, cinnamaldehyde also decreased visceral fat deposition, partly mediated by the activation of interscapular BAT, as evidenced by the upregulation of UCP1 expression levels, in high fat and high sucrose diet-fed mice [97].…”
Section: Phytochemicals In Obesitymentioning
confidence: 99%
“…It is commonly used in the treatment of cold fever. Modern pharmacological studies revealed that CR could not only exhibit antineuroinflammatory (Yang, Cheng, Yang, Wang, & Du, 2017), antidiabetic (Han, Jung, Bae, Kang, & Park, 2013) and anti-gastric lesions effects (Joohee, Je-Hyuk, Ki Hwan, & Choon-Sik, 2011), but also have anti-bacterial (Liu et al, 2007) and chemopreventive (Park, Lee, Oh, Bae, & Kim, 2005) functions. The main bioactive components of CR are phenolics such as cinnamic acid (Wu, He, Xu, Bi, & Li, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Pueraria lobata extract also inhibited tert -butyl hydroperoxide-induced ROS generation [ 37 ]. An extract of Cinnamomum cassia twigs inhibited adipocyte differentiation via activation of the insulin signaling pathway in 3T3-L1 preadipocytes [ 38 ]. Ephedra sinica extract exerted antioxidant effects by accelerating free radical scavenging activity and oxidant reducing power [ 39 ].…”
Section: Discussionmentioning
confidence: 99%